Characterization, mechanical, corrosion, and in vitro apatite-formation ability properties of hydroxyapatite-reduced graphene oxide coatings on Ti6Al4V alloy by plasma electrolytic oxidation - Erfan Mohammadipour; Mohammad Ghorbani (Journal of Materials Research and Technology)
Hydroxyapatite-reduced graphene oxide (HA/rGO) nanocomposite coatings were developed on Ti6Al4V alloy using plasma electrolytic oxidation (PEO). The PEO electrolyte comprised calcium acetate (C4H6CaO4) and calcium glycerophosphate (C3H7O5CaP). Prior to integrating reduced graphene oxide into the coating solution, parameters such as voltage and current density were optimized using scanning electron microscopy (SEM). The influence of various current densities and graphene concentrations on coating properties was analyzed. Coating phase structures, surface morphologies, functional groups, and chemical compositions were characterized by X-ray diffraction (XRD), SEM, attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), and energy dispersive spectroscopy (EDS). Raman spectroscopy confirmed the presence of graphene in the coatings. Surface morphology examinations revealed that surface cracks appeared at voltages above 350 V due to thermal stresses. Increasing current density reduced the number of porosities but increased pore size. Adding graphene to the solution to form HA/rGO coatings further decreased both the number and size of porosities. XRD analysis identified phases of titanium, anatase, rutile, titanium phosphide, tri-calcium phosphate (TCP), and hydroxyapatite in the coatings. Corrosion properties were assessed via potentiodynamic polarization tests in simulated body fluid (SBF) solution. Tribological and mechanical properties were evaluated by pin-on-disk and microhardness, respectively. The in vitro apatite-formation ability of the coatings was assessed by immersion in SBF at 37 °C, with ion concentration changes measured by inductively coupled plasma spectrometry (ICP). Results indicated that increasing current density reduced porosities and increased the Ca/P ratio.